Robot for boiler header inspection "LS-01" - Baharuddin M.Z.; Saad J.M.; Anuar A.; Ismail I.N.; Maisurah N.; Basri H.; Roslin N.S.; Mohideen S.S.K.; Jalal M.F.A.; Sahari K.S.M. (Elsevier Ltd, 2023)
Inspection of boiler headers is routinely being performed in Tenaga Nasional Berhad (TNB) thermal power plants. It is very important to inspect boiler header from time to time to check for signs of possible failures because they are thick walled and exposed to various operating conditions. The currently used method is to insert a fiber optic camera probe into the boiler header entry manually by human. This work is very tedious and the inspector often has difficulties to acquire full coverage of the inner wall images. Therefore, it is proposed that a robotic system is developed to carry the fibre optic probe into the boiler headers and assist in a more efficient and reliablen boiler header inspection. The developed robot prototype must be small enough to enter the header and must also have the capability to traverse the whole length of boiler header while carrying the existing fibre optic probe as well as cater for boiler header with different diameters. LS-01, presented in this paper, is the first boiler header inspection robot prototype developed, equipped with semi-intelligent system and adjustable entry platform, and is capable of traversing inside boiler headers with various tube configurations. It has been tested in accordance with the engineering requirements set by TNB. Testing has shown the potential of the robot to be applied in a real boiler header inspection processes. 2012 The Authors.